GUIDANCE AND COUNSELING MANAGEMENT: A SCIENTIFIC APPROACH TO IMPROVING STUDENTS' MENTAL HEALTH - Zakaria, Nanang; Faisal, Muhammad; Malini, Hema; Sobirin, Sobirin; Marzuki, Marzuki (LP2M IAI Al-Khairat Pamekasan, 2024)
The objective of this research is to explore the management of guidance and counseling as a scientific approach to enhancing students' mental health. The method employed in this study is qualitative research, specifically using a case study design. The choice of a case study is justified as it allows the researcher to gain in-depth insights into the context, processes, and complexities of the phenomenon under investigation. The findings of this research illustrate that the role of guidance and counseling (BK) teachers in state high schools in West Kalimantan, Indonesia, in safeguarding students' mental health is not merely reactive but also proactive. BK teachers apply a scientific approach involving observation and interviews to understand the holistic needs and challenges faced by students. Additionally, they utilize a variety of counseling techniques, including individual counseling, group counseling, cognitive-behavioral approaches, and art and play therapy, to provide tailored support based on individual student needs.